2011
DOI: 10.1098/rsta.2011.0060
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and interpreting the ocean uptake of atmospheric CO 2

Abstract: The oceans are an important sink for anthropogenically produced CO 2 , and on time scales longer than a century they will be the main repository for the CO 2 that humans are emitting. Our knowledge of how ocean uptake varies (regionally and temporally) and the processes that control it is currently observation-limited. Traditionally, and based on sparse observations and models at coarse resolution, ocean uptake has been thought to be relatively invariant. However, in the few places where we have enough observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…However, as the ocean carbon sink is sensitive to climate as well as atmospheric CO 2 , models predict a future weakening of the CO 2 uptake rate in response to ongoing climate change, resulting in a positive carbon-climate feedback [Friedlingstein et al, 2006]. The effort to identify this climate-carbon feedback promoted the investigation of trends in ocean carbon uptake [Le Quéré et al, 2007;Schuster and Watson, 2007;Thomas et al, 2008;Schuster et al, 2009;Metzl et al, 2010;Watson et al, 2011] in order to detect substantial deviations from the expected response to rising atmospheric CO 2 . However, the causes of the recent variations in the ocean carbon uptake over the last decades are still poorly understood [Le Quéré et al, 2007;Lovenduski et al, 2008;McKinley et al, 2011;Bates, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…However, as the ocean carbon sink is sensitive to climate as well as atmospheric CO 2 , models predict a future weakening of the CO 2 uptake rate in response to ongoing climate change, resulting in a positive carbon-climate feedback [Friedlingstein et al, 2006]. The effort to identify this climate-carbon feedback promoted the investigation of trends in ocean carbon uptake [Le Quéré et al, 2007;Schuster and Watson, 2007;Thomas et al, 2008;Schuster et al, 2009;Metzl et al, 2010;Watson et al, 2011] in order to detect substantial deviations from the expected response to rising atmospheric CO 2 . However, the causes of the recent variations in the ocean carbon uptake over the last decades are still poorly understood [Le Quéré et al, 2007;Lovenduski et al, 2008;McKinley et al, 2011;Bates, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…Among these regions potentially impacted by anthropogenic forced climate change, the North Atlantic has been extensively studied over the three last decades (Watson et al, 2011;Schuster et al, 2009;Brown et al, 2010;Metzl et al, 2010;Corbière et al, 2007;McKinley and Follows, 2004;McKinley et al, 2011). Debate prominently arises from disagreement between causes of trends in the North Atlantic carbon sink estimated from data or numerical model output.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of in situ observations, several authors (i.e. Corbière et al, 2007;Watson et al, 2011;Brown et al, 2010;Metzl et al, 2010) have reported a more rapid growth in surface ocean pCO 2 than in atmospheric pCO 2 , which translates into a decline of the net ocean carbon uptake over the last decade. Possible mechanisms driving this decline are associated to climate-induced modifications of both oceanic and atmospheric dynamics, e.g., rising sea-surface temperature (Corbière et al, 2007), increasing ocean stratification (Schuster et al, 2009) or changes in horizontal oceanic currents owing to a shift in the North Atlantic Oscillation (Thomas et al, 2007;Schuster et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In this work we have analysed solely the effects of the choice between various published empirical wind-driven gas-transfer parameterizations. The North Atlantic is one of the regions of the world ocean best covered by CO 2 fugacity measurements (Watson et al, 2011), the coverage of the Arctic seas is much poorer, especially in winter .…”
Section: Introductionmentioning
confidence: 99%